Menyelami Sejarah Peradaban Islam Dari Konsep Hingga Metode Penggalian Yang Mendalam - Elsania Revansya Wulan Aprilia; Tsaniah Marta Rizqi Nur Baiti; Baiq Aziza Suci Ramadhania; Hana Sofwanul Muhit; Umar al Faruq (GLOBAL SCIENTS PUBLISHER, 2024)
The history of Islamic civilization encompasses the development of knowledge, technology, art, and culture built by Muslims from the early days until today. This article discusses several important aspects, such as the definition of Islamic civilization, the concepts of culture and civilization, and the methodologies used to explore this history. The history of Islamic civilization also demonstrates how the interaction between religion and the historical context in Muslim societies shaped Islamic culture, which is closely tied to religious values. In this regard, Islamic culture not only covers spiritual aspects but also social, political, and intellectual aspects that developed over time. Islamic civilization itself represents the collective achievements of Muslims in various fields, including knowledge, art, and technology, which had a significant impact on the progress of the world in its time. Studying the history of Islamic civilization contributes greatly to understanding Islam, ethics, and the importance of preserving its cultural heritage. Moreover, by studying this history, we can uncover universal values taught by Islam, such as justice, knowledge, and humanity, which remain relevant today.